1985
DOI: 10.1111/j.1745-4603.1985.tb00678.x
|View full text |Cite
|
Sign up to set email alerts
|

Interdependency and Underlying Dimensions of Sensory Textural Characteristics of Selected Foods2

Abstract: Sensory texture profile data for butters, cheeses, fish gels, frankfurters, peanut butters, raw potatoes, and baked sweet potatoes were subjected to principal component analysis to study the interdependence and the underlying dimensions of the sensory textural characteristics. The results indicated that the character notes used by the panel to describe the texture profile of each product were not entirely independent but formed a pattern of interdependency in the underlying dimensional structure. The texture p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…The I-COH and M-CHEW variables which define this factor were also correlated with moistness and firmness variables in F1. The above pattern of interdependency of sensory texture notes is in accordance with that of baked sweetpotatoes reported by Syarief et al (1985). The close interrelationships among sensory texture notes of fish, meat and egg white gels have also been reported (Hamann and Webb 1979;Montejano et al 1985).…”
Section: Correlation Analysissupporting
confidence: 86%
“…The I-COH and M-CHEW variables which define this factor were also correlated with moistness and firmness variables in F1. The above pattern of interdependency of sensory texture notes is in accordance with that of baked sweetpotatoes reported by Syarief et al (1985). The close interrelationships among sensory texture notes of fish, meat and egg white gels have also been reported (Hamann and Webb 1979;Montejano et al 1985).…”
Section: Correlation Analysissupporting
confidence: 86%
“…A negative correlation between firmness and spreadability was reported in creamery butters and peanut butters investigated by Syarief et al . (). The measurements of firmness conflict somewhat with the hardness (Table ), but are likely because of the differences in the probes employed and their geometry.…”
Section: Resultsmentioning
confidence: 97%
“…Only the peanut butters containing 5.0% dry-blanched PS, light-roasted PS above 2.5%, and 5.0% medium-roasted PS showed an increase in firmness. A negative correlation between firmness and spreadability was reported in creamery butters and peanut butters investigated by Syarief et al (1985). The measurements of firmness conflict somewhat with the hardness (Table 3), but are likely because of the differences in the probes employed and their geometry.…”
Section: Spreadabilitymentioning
confidence: 90%
See 1 more Smart Citation
“…Previous studies of the texture of carcass meats (Harries et a/ 1972;Frijters 1976;Dransfield et a/ 1984) and meat products such as frankfurters (Syarief et a/ 1985) and burgers have shown that the major source of variation derives from mechanical attributes describing the initial stages of mastication. A similar result was found here, where 'initial firmness', 'skin toughness' and 'meatiness' comprised the toughness/tenderness component.…”
Section: Sensory Components Of Sausage Qualitymentioning
confidence: 99%